PENGARUH BUDAYA ORGANISASI DAN PENERAPAN STANDAR ASUHAN KEPERAWATAN TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP RS. MARTHA FRISKA BRAYAN MEDAN - Sridama Yanti Harahap; Ritha F Dalimunthe; Masnelly Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
The performance of executing nurses is one of the important factors in materializing the quality of nursing service at a hospital. Every hospital has problem with the performance of nurses especial those serving in the in-patient wards, and this problem is also experienced by Martha Friska Hospital Brayan Medan. The factors of organizational culture and nursing care standard application are still suspected to have influenced the performance of the nurses. The purpose of this explanatory survey study was to analyze the influence of organizational culture and nursing care standard application on the performance of the nurses serving in the in-patient wards of Martha Friska Hospital Brayan Medan. The population of this study was 125 nurses serving in the in-patient wards at Martha Friska Hospital Brayan Medan and 56 of them were selected to be the samples for this study. The primary data for this study were obtained through observation and questionnaire distribution and secondary data obtained through studying the documents available at Martha Friska Hospital Brayan Medan. The data obtained were analyzed through multiple linear regression tests at level of confidence 95%. The result of this study showed that the performance of the nurses serving in the in-patient wards at Martha Friska Hospital Brayan Medan was 51.8% and this belonged to inadequate category. The result of multiple linear regression tests showed that the variables of nurses’ involvement (p = 048), nurses’ adjustment (p = 0.004), nurses’ consistency (p = 0.006), mission of organization (p = 0.010), and the application of nursing care standard (p = 0.002) had influence on the performance of nurses in the in-patient wards at Martha Friska Hospital Brayan Medan. The management of Martha Friska Hospital Brayan Medan is suggested (1) Establishing the nursing care standards, directive service, job description and consistent guidance in health service provision,(2) Establishing the administration staff for every nurse station which job description is to calculate the cost of clients care in ward (3) Classification the patient-wards based on patient diagnosis (4) the nurses should improve their individual performance through the comprehensive application of nursing care standard referring to the need of clients.